Risk Factor Analysis of Delayed Intracerebral Hemorrhage After Coil Embolization of Unruptured Cerebral Aneurysms - Son, Wonsoo; Kang, Dong-Hun (Frontiers in Neurology, 2020)
Background We sought to determine the risk factors of delayed intracerebral hemorrhage (d-ICH) after coil embolization for unruptured aneurysms (UIA). Methods In a total of 539 aneurysms were enrolled in this study. Ruptured cases and flow diverter cases were excluded. All aneurysms enrolled this study were treated with stent-assisted or simple coiling techniques. Before the procedure all patients administered dual antiplatelet therapy (DAPT). After the procedure, patients who underwent the stent-assisted coil embolization were given DAPT and patients who underwent simple coiling were given only single antiplatelet therapy (SAPT) only during their admission. The response of antiplatelet agent was assessed the day before the procedure with The VerifyNow assay. Diffusion-weighted imaging (DWI) MRI and CT were obtained routinely the next day after the procedure. d-ICH was defined as intracerebral hemorrhagic lesion identified in follow up CT at least from 48 hours after the procedure. Results The larger positive lesion on day 1 DWI MRI (p=0.001), value of PRU (p=0.002) and inhibition rate (p=0.025) were considered as meaningful risk factors for d-ICH in univariate analysis. Accordingly, Larger DWI positivity (OR=83.73, 95% CI=11.132-712.886, P=0.001) and PRU (OR=0.98, 95% CI=0.972-0.999, P=0.033) reached to statistical significance in multivariate analysis Conclusions Thromboembolic infarction may work as an initiating factor, and antiplatelet medication may work as an aggravating factor. We might suggest that a tailored reduction in antiplatelet agents could be helpful to reduce d-ICH when a larger volume of post-thromboembolic infarction is seen on 1-day follow-up DWI MRI.